2015
DOI: 10.1159/000438465
|View full text |Cite
|
Sign up to set email alerts
|

Chromium Supplementation and the Effects on Metabolic Status in Women with Polycystic Ovary Syndrome: A Randomized, Double-Blind, Placebo-Controlled Trial

Abstract: Background: The aim of the present study was to evaluate the beneficial effects of chromium intake on markers of insulin metabolism and lipid profiles in women with polycystic ovary syndrome (PCOS). Methods: In a prospective, randomized, double-blind, placebo-controlled trial, 64 women with PCOS were randomized to receive 200 µg chromium picolinate supplements (n = 32) or placebo (n = 32) for 8 weeks. Fasting blood samples were obtained at baseline and 8 weeks after the intervention to quantify markers of insu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
49
0
4

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(56 citation statements)
references
References 32 publications
3
49
0
4
Order By: Relevance
“…Study quality was assessed using a scale proposed by the Cochrane Back Review Group, and the results are presented in Table . Overall, three (50.00%) of the included studies were classified as high quality, and the other three (50.00%) were classified as moderate quality . The qualified trials scored from 5 to 11 points (mean, 8.33 ± 1.97).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Study quality was assessed using a scale proposed by the Cochrane Back Review Group, and the results are presented in Table . Overall, three (50.00%) of the included studies were classified as high quality, and the other three (50.00%) were classified as moderate quality . The qualified trials scored from 5 to 11 points (mean, 8.33 ± 1.97).…”
Section: Resultsmentioning
confidence: 99%
“…In detail, four trials (66.67%) adopted adequate random sequence generation and allocation concealment, and three trials (50.00%) had similar baseline conditions. Most trials (83.33%) used participant blinding or provider blinding, whereas one trial (16.67%) reported the outcome assessor blinding . Four studies did not utilize co‐interventions, and two used metformin .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Chromium supplementation can significantly cut down total cholesterol (TC) and low-density lipoprotein (LDL) levels in Type 2 diabetes (T2D) subjects [710], women with polycystic ovary syndrome [11] and high fat diet rats [12,13]. The suggested minimum daily intake of chromium is 30 μg.…”
Section: Introductionmentioning
confidence: 99%
“…149 Another study found that 200 mg/day chromium supplementation for 8 weeks among PCOS had favorable effects on fasting insulin, IR and insulin sensitivity. 150 Moreover, 5 mg/day folate supplementation for 8 weeks among PCOS had beneficial effects on inflammatory factors and biomarkers of oxidative stress. 151 In conclusion, there is insufficient evidence to recommend micronutrient supplements for women with PCOS at this time.…”
mentioning
confidence: 99%